The Role of Cloud Computing in Enhancing Internal Control: A Field Study on Libyan Commercial Banks in the Eastern Region (Sirte University Journal of Humanities, 2026)
This study aims to identify the role of cloud computing in enhancing internal control within the investigated Libyan commercial banks. To achieve this objective, the study adopted an inductive-deductive approach, utilizing a multi-stage sample that included three banks in the eastern region (Wahda Bank, National Commercial Bank, and Bank of Commerce & Development). The study targeted departments of internal audit, information security, compliance, accounting, and reporting, using a simple random sampling technique. Data were collected via an electronic questionnaire, resulting in 70 valid responses for statistical analysis using the SPSS software. Descriptive statistics were employed to determine general trends of respondents, while inferential statistics were used to test the study's hypotheses. The findings revealed a positive relationship and a statistically significant impact of cloud computing dimensions (Security and Privacy, Availability and Flexibility, Advanced Data Analytics, and Cost Reduction) on enhancing internal control in Libyan commercial banks. The study recommended leveraging the advantages of cloud computing to address internal control weaknesses highlighted by the Libyan Audit Bureau through the adoption of integrated technological solutions that ensure the efficiency of supervisory work and data security in Libyan commercial banks.
Keywords: Cloud Computing; Internal Control; Libyan Commercial Banks